2020
DOI: 10.1097/aci.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis usefulness for idiopathic anaphylaxis

Abstract: Purpose of review Molecular diagnosis has become an indispensable tool in allergy. In suspected idiopathic anaphylaxis, it is mandatory to extend the diagnostic search to its limits. The current review evaluates how molecular diagnosis allows to identify a number of difficult to prove potential culprits. Recent findings Depending on different geographical areas, it has been shown that the number of anaphylaxis labelled as idiopathic may decrease by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…MD has been useful to identify causes of anaphylaxis previously labelled as idiopathic. In the case of singleplex assays, the clinician may choose the single components to be tested as for example is the case of delayed meat anaphylaxis, which can be diagnosed by detecting sIgE to -gal (galactose--1,3-galactose) or sIgE to -5-gliadin (Tri a 19) in cases of suspected wheat dependent exerciseinduced anaphylaxis or other known allergens [61].…”
Section: Is MD Useful In the Study Of An Idiopathic Anaphylaxis (Ia)?mentioning
confidence: 99%
See 1 more Smart Citation
“…MD has been useful to identify causes of anaphylaxis previously labelled as idiopathic. In the case of singleplex assays, the clinician may choose the single components to be tested as for example is the case of delayed meat anaphylaxis, which can be diagnosed by detecting sIgE to -gal (galactose--1,3-galactose) or sIgE to -5-gliadin (Tri a 19) in cases of suspected wheat dependent exerciseinduced anaphylaxis or other known allergens [61].…”
Section: Is MD Useful In the Study Of An Idiopathic Anaphylaxis (Ia)?mentioning
confidence: 99%
“…Another approach is the use of multiplexed assays, in which a high number of individual allergen molecules are tested simultaneously. Molecular diagnosis arrays allow their use as a form of 'screening' tool in anaphylaxis to assess sensitization of the patient identifying the potential triggers [61].…”
Section: Is MD Useful In the Study Of An Idiopathic Anaphylaxis (Ia)?mentioning
confidence: 99%
“…Algunos de los alergenos identificados en pacientes son alfa-gal, nsLTP, oleosinas y omega-5-gliadina. 1,2 ANAFILAXIA Y DIAGNÓSTICO MOLECULAR Todavía existe una necesidad importante de desarrollar biomarcadores para diagnosticar y predecir el riesgo que tiene un individuo de presentar anafilaxia. El diagnóstico por componentes ha permitido mejorar nuestra capacidad para identificar fenotipos clínicos específicos y ha evolucionado la comprensión de los perfiles de sensibilización, por lo que…”
Section: Abordaje Molecular En El Paciente Con Antecedente De Anafilaxiaunclassified
“…In thinking about the use of IgE microarrays, there are certain clinical scenarios in which the ability to test a large panel of allergens in a single test could have real advantages (Table 4). These include the work-up of idiopathic anaphylaxis, 45 pollen-food allergy syndrome, 46 local allergy, [47][48][49][50] and food allergy. 51,52 Heaps et al 25 investigated 110 cases labeled as idiopathic anaphylaxis based on standard evaluation and found that ISAC testing identified likely culprits in an additional 20% of these cases.…”
Section: Clinical Scenarios That Could Favor Ige Microarraymentioning
confidence: 99%